Pengaruh Layanan SMS Gateway Terhadap Kepatuhan Minum Tablet Tambah Darah Pada Anggota Teman Sebaya Tanggap Anemia Di Puskesmas Bangsri Kabupaten Jepara - Suwarni, Sri; Khotimah, Devi Syahrilia; Nahak, Martinus; Widyastuti, Rini (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Based on the data from the Basic Health Research (Riskesdas) in 2018, 80,9% of female teenagers received blood tablets in their schools while 19.1% of them did not receive the tablets from their schools. From the number of the female students who got blood tablets, furthermore, it was found that the number of the tablets taken was only <52 tablets or as many as 98,6%; which means only 1,4% of female students who took ≥52 tablets (Kemenkes, 2016). Teman Sebaya Tanggap Anemia (friends of the same age responsive to anemia) is the special term for a group of people considered as the blood tablet recipients. Some interventions can be conducted to improve the patients’ medical compliance such as medical information service, distributing medical leaflets, sending short reminders, and utilizing alarm (Susanto, 2017). The purpose of this research is to measure the medication compliance level of Teman Sebaya Tanggap Anemia (TSTA) in taking blood tablets at Puskesmas Bangsri, Jepara Regency and to comprehend the influence of the Short Message Service (SMS) gateway on such compliance. The quasi-experimental was employed in this research, and the prospective data were collected from February to April 2019. The data were then analyzed using the Chi Square test and the Wilcoxon test. The result showed that the percentage of compliance was only 34.57% before the treatment was given, and the SMS gateway service gave significant influence on the compliance of TSTA (p 0.00 < 0.05) In addition, the Wilcoxon test result also showed the same result (p 0.00 < 0.05), and it proved that there was significant difference in the compliance before and after the treatment; therefore the SMS gateway service was effectively proven in improving the medication compliance percentage from 34.57% to 87.23%.